Evaluation and selection of turmeric (Curcuma longa L.) genotypes - Azhakiamanavalan, M Ganga, K A Shanmugasundaram, T Thangaraj, R S (Journal of Spices and Aromatic Crops, 2001)
Fifteen genotypes of turmeric (Curcuma longa L.) from five states of India were evaluated for yield and curcumin content. Among them, PTS-43 yielded 33.86 t ha-1 fresh rhizome, 7.17 t ha-1 cured rhizome, 5.36% curcumin and 21.17 % recovery of cured rhizome as against 28.00 t ha-1, 4.48 t ha-1, 3.56 % and 16.00% respectively in BSR-2, the local check and 26.69 t ha-1, 5.69 t ha-1 4.84% and 21.33%, respectively in the national check (var. Roma).